Contrasting Specific English Corpora: Language Variation - Carrió Pastor, María Luisa (International Journal of English Studies, 2010)
The scientific community has traditionally considered technical English as neutral and objective, able to transmit ideas and research in simple sentences and specialized vocabulary. Nevertheless, global communication and intense information delivery have produced a range of different ways of knowledge transmission. Although technical English is considered an objective way to transmit science, writers of academic papers use some words or structures with different frequency in the same genre. As a consequence of this, contrastive studies about the use of second languages have been increasingly attracting scholarly attention. In this research, we evidence that variation in language production is a reality and can be proved contrasting corpora written by native writers of English and by non-native writers of English. The objectives of this paper are first to detect language variation in a technical English corpus; second, to demonstrate that this finding evidences the parts of the sentence that are more sensitive to variation; finally, it also evidences the non-standardisation of technical English. In order to fulfil these objectives, we analysed a corpus of fifty scientific articles written by native speakers of English and fifty scientific articles written by non-native speakers of English. The occurrences were classified and counted in order to detect the most common variations. Further analysis indicated that the variations were caused by mother tongue interference in virtually all cases, although meaning was only very rarely obscured. These findings suggest that the use of certain patterns and expressions originating from L1 interference should be considered as correct as standard English.